Introduction to Electronic Commerce and Social Commerce - Turban, Efraim; Whiteside, Judy; King, David; Outland, Jon (Springer, 2017)
The global economic crisis of 2009–2014 forced organizations to reduce expenses in an environment of reduced economic activities. One of the most popular cost-reduction activities is conducting more business online. Actually, we are experiencing one of the most important changes to our daily lives—the move to an Internet-based society. Internet World Stats (internetworldstats. com) reported in 2014 that more than 83% of the North American population surf the Internet (Fall 2015). The large number of people on the Internet is one of the major drivers of conducting business online, which is known as electronic commerce, or in its broader scope as e-business. Electronic commerce (EC) describes the manner in which transactions take place over networks, mostly the Internet. It is the process of electronically buying and selling goods, services, and information. Certain EC applications—such as buying and selling stocks and airline tickets on the Internet—are growing very rapidly, exceeding non-Internet trades. But EC is not just about buying and selling; it is also about electronically communicating, collaborating, and discovering information. It is about e-learning, e-government, e-health, social networks, and much more. Electronic commerce has an impact on a significant portion of the world, including developing countries, affecting businesses, professions, and most importantly people.